ІННОВАЦІЙНІ МЕТОДИ ФОРМУВАННЯ ВОКАЛЬНОЇ КУЛЬТУРИ МАЙБУТНЬОГО ВЧИТЕЛЯ МУЗИКИ (Педагогіка вищої та середньої школи, 2022)
The article touches on the problem of professional training of music teachers, the main aspect of which is the usage of effective methods for formation of vocal culture offuture music teachers. It's suggested some ways and methods of further perfection in the vocal performing skill of students during the process of specially organized work.